Reduksi Hotel Dan Homestay Sebagai Akomodasi Pariwisata Dalam Fungsi Sortir Online Travel Agent - Reinaldo Rafael; I Wayan Kiki Sanjaya (Cultoure: Jurnal Ilmiah Pariwisata Budaya Hindu, 2020)
Online travel agent (OTA) has been the main connection for guests to reach a tourism destination, where the algorithm of “sort” function enables a guest to find and pick any accommodation, attraction, accessibility, and amenity to his/her wants and needs in a single click. This study will discuss how such single click reduces (combine and generalize) every hotel and homestay within an OTA, hence experience as homestay’s main value has become irrelevant as an indicator of deciding the accommodation. The purpose of this study is to start an academic discussion about assumptions of modernity in tourism, a topic that has been taken for granted (purposefully?) so often. Using qualitative content analysis as data analysis method, this study did purposeful sampling interviews with hotel and homestay practitioners in Ubud, mainly to divulge a new perspective about practical implications of modernity in tourism. Keywords: Reduction, Hotel, Homestay, Accommodation, Modernity.